Mathematics - Johnson, David B. (Recording for the Blind & Dyslexic, 2004)
MATHEMATICS: A PRACTICAL ODYSSEY is a market leader, well known for its clear writing and unique variety of topics, including its accessible chapters on logarithms and exponential functions, calculus and Markov chains. Johnson and Mowry's text emphasizes the practical applications and the history of mathematics. It illustrates to students how mathematics is relevant to their education, human history, and culture. The authors effectively demonstrate how learning algebraic concepts allows students to understand more about how logic, probability, statistics, finance, geometry, matrices, logarithms, calculus, and other topics are vital to everyday life